Endovascular treatment of acute ischemic stroke in childhood: A comprehensive literature review based on the experience of a single center - Guglielmo Pero; Francesco Ruggieri; Antonio Macera; Mariangela Piano; Caroline Regna Gladin; Cristina Motto; Amedeo Cervo; Arturo Chieregato (European Journal of Radiology Open, 2023)
Acute ischemic stroke (AIS) in childhood is a relatively rare but significant condition that can result in long-term disabilities. There is a lack of standardized strategies for diagnosing and treating pediatric AIS due to limited evidence-based data on thrombolytic and endovascular treatments in children. This comprehensive literature review focuses on the experience of a single center in Italy and aims to highlight the main peculiarities of endovascular treatment (EVT) for AIS in childhood.The review covers the diagnostic workup, the endovascular procedures, and the need for a specific thrombectomy program for pediatric AIS.The review discusses the indications and considerations for thrombectomy in children, including the risk of complications and the challenges of extrapolating results from adult studies. The diagnostic protocols for pediatric AIS are also discussed, emphasizing the use of MRI to avoid X-ray and contrast medium exposure in children.The combination of intravenous thrombolysis and mechanical thrombectomy has been examined, considering the differences between pediatric and adult thrombi. Technical considerations related to the size of pediatric patients are addressed, including the use of large bore catheters and potential concerns with access points.The organization of a thrombectomy program for pediatric AIS is discussed, emphasizing the need for specialized facilities and expertise.Although evidence for EVT in the pediatric population is based on case series, the importance of specialized centers and the lack of validated guidelines are evident.